MANICOMIALIDADES E CUIDADOS MOLECULARES: CARTOGRAFIAS DAS RELAÇÕES EM UM CAPS II VITÓRIA - Eduardo, Gustavo Alves (2021)
This dissertation launches itself to the cartography of care relationships in a Psychosocial Care Center II (CAPS), which is configured as a substitute service in mental health in the city of Cariacica. It would be a study that takes place in a complex tangle between four thematic outlines: care; policies, control technologies and health. In this bias, we approached in the first part of the work, considering the pertinence that it is to think what we have named as care in our clinical-institutional practices, in a ritualistic or in an exercise arising from the middle of our relationships. In the second part, given the time we live, it would be fitting to think that our ways of life are registered by agencies. These cross the entire reality of existential territories with their political multiplicities, thus producing effects in the fabric of subjectivities in everyday life. In the third part, we can articulate some discussions that involve thinking about the emergence of public mental health policy through history, which is equivalent to knowing its developments over time, as well as understanding the control technologies. We realized that care relationships, especially between professionals and patients-users of the service, can occur in what we register as molecular care, in its inventive and micropolitical flow. Thus, in the fourth part, health and other crazy things we have some discussions based on what was understood in the research dialogues as a concept of health, group relations, delusions and hallucinations. Therefore, when elaborating the final considerations, it was understood that the ethical exercise of thought and the cultivation of practices is, in fact, an invitation to care for relationships, since the existential territories are crossed by a multiplicity of policies and modulations affective. In this context, this research is part of an ethical-political commitment to the care relationships in the territory of public mental health policy today.